The Microvascular Volume of the Achilles Tendon Is Increased in Patients With Tendinopathy at Rest and After a 1-Hour Treadmill Run. (October 2013) - Pingel, Jessica; Harrison, Adrian; Simonsen, Lene; Suetta, Charlotte; Bülow, Jens; Langberg, Henning
Background: Achilles tendinopathy (AT) is initiated asymptomatically and is therefore often discovered at a very late stage. Purpose: To elucidate whether the microvascular volume (MV) of the Achilles tendon is elevated in patients with AT compared with healthy controls during pre-exercise rest, after acute exercise, and 24 hours after exercise. Additionally, this study investigated the muscle activation pattern of the gastrocnemius muscle and the relative elasticity of the Achilles tendon during a 1-hour treadmill run in healthy patients and in patients with AT. Study Design: Controlled laboratory study. Methods: Real-time harmonic contrast-enhanced ultrasound (CEU) measurements of the MV of the Achilles tendon were taken in 18 volunteers (9 patients with AT, 9 healthy controls). The CEU analyses were conducted before exercise, immediately after a 1-hour treadmill run, and 24 hours after exercise. Surface electromyography (EMG) signals of the gastrocnemius were recorded continuously during the 1-hour treadmill run. Results: In both the controls and the patients with AT, the MV of the Achilles tendon was increased after exercise as compared with before exercise ( P < .005). Additionally, the MV signal was significantly larger in the patients with AT before, immediately after, and 24 hours after the running exercise compared with values in healthy controls ( P < .0001). The muscle activation pattern differed in patients with AT compared with controls in that controls had increased EMG amplitudes at the end of the 1-hour treadmill run in the medial and lateral gastrocnemius ( P < .0001). Moreover, patients with AT had approximately 15% less elastic Achilles tendons at the beginning of the 1-hour treadmill run, a condition that did not change because of exercise. Conclusion: Acute exercise increases the MV of the Achilles tendon in healthy patients and patients with AT in a similar manner. However, patients with AT have a significantly larger MV at all time points compared with healthy patients, supporting the hypothesis that microvascular changes may be involved in the pathogenesis of tendinopathy. Clinical Relevance: This study underlines that tendon flexibility is altered in patients with AT and that CEU is a promising tool to establish the early diagnosis of this condition.